Psychophysiological questionnaire which concerns the professional adaptation of participants in the Antarctic expedition - G. Pyshnov; Y. Moiseyenko; L. G. Vysotskaya (Ukrainian Antarctic Journal, 2013)
The article contains the results of psycho-physiological examination wintering (Ukrainian Antarctic expedition) and a group of students (before exams). Using factor analysis of test results (eight versions of the questionnaires, which included more than 500 questions) identified additional factors that play a leading role in the evaluation of the individual psychological characteristics to work in the special conditions of the Antarctic. Developed and improved a new test-administered questionnaire, which allows testing of candidates for the winter on the basis of "professional adaptability in the special conditions." With the proper credibility estimates reduced testing time.